Sunday TV Mass as a Ritual Communication among the youth (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Sunday TV Mass (STVM) is one of the Catholic Churchs initiatives for evangelization via media. Primarily produced to spread the Good News, it is specifically for the sick and physically incapable since they cannot go to churches to attend Mass and fulfill their Sunday obligation. However, since the broadcast Mass is communicated through a mass medium and is exposed to a wider audience than necessarily targeted, some people, the adolescents (youth) in particular, make STVM an excuse to forego Mass attendance in their respective churches. This experimental study will focus on STVM on its role as evangelizer and catalyst to ritual formation. James Careys theory of Ritual Communication describes this practice as an enabler to the creation of a community of believers among the youth and George Gerbners Cultivation Theory on how television creates a worldview that unravels ritualistic experience by watching STVM. The respondents of the study are 40 high school students of Angelicum College.  Selected purposively, the students were instructed and monitored to watch STVM for four Sundays. These students are top achievers in their Religion subjects and are exposed to different religious activities in their school.